2020
DOI: 10.5430/ijhe.v9n2p280
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inductive and Deductive Teaching on EFL Undergraduates’Achievement in Grammar at the Hashemite University in Jordan

Abstract: This current study aims at investigating the impact of using inductive and deductive teaching upon EFL undergraduate students’ achievement at the Hashemite University. More specifically, the study attempts to explore the effect of using inductive and deductive approach on students’ achievement in some grammatical issues included a book adopted for teaching Grammar 2 in the Department of English Language and Literature. The research instrument used is a pre-post-test developed by the researchers. Two groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
(10 reference statements)
0
9
1
Order By: Relevance
“…However, the results differ from those of Negahdaripour and Amirghassemi (2016), Wang (2012), Mohammed and Jaber (2008), which supported a deductive approach. The findings of this study also in contrast with Anani (2017), Benitez-Correa et al, (2019), Obeidat and Alomari (2020), Putthasupa and Karavi (2010), who reported that the inductive approach was more effective in teaching grammar.…”
Section: Discussion Limitations Recommendations For Action and For Further Researchcontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the results differ from those of Negahdaripour and Amirghassemi (2016), Wang (2012), Mohammed and Jaber (2008), which supported a deductive approach. The findings of this study also in contrast with Anani (2017), Benitez-Correa et al, (2019), Obeidat and Alomari (2020), Putthasupa and Karavi (2010), who reported that the inductive approach was more effective in teaching grammar.…”
Section: Discussion Limitations Recommendations For Action and For Further Researchcontrasting
confidence: 99%
“…The findingsindicated that the inductive approach was more effective than the deductive approach.In their experimental study, Putthasupa and Karavi (2010) investigated whether the use of the inductive approach could minimise students' grammatical errors inessaywriting.The objectives of the study were to compare the effectivenessof the inductive approach against 'regular lectures'and to identify students' errors. The findings indicated that thatthe inductive approachhad a positive effect on the teaching of grammar by minimising grammatical errors.In a recent study, Obeidat and Alomari (2020) explored the effect of the deductive and inductive approaches on English as a Foreign Language (EFL)undergraduates' achievement in grammar at the Hashemite University in Jordan. To achieve its objectives, the study used a wide range of grammaticalitemsin sentence correction.The findings showed significant differences infavour of the inductive approach.…”
Section: Studies Supporting Inductive Instructional Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an Inductive Model in the teaching and learning process can enhance these skills for science students. The rationale for using the Inductive Model to enhance students' critical thinking skills is supported by previous research findings [6], [7]. The previously research finding showed that using inductive model increased students' result in Jordan (pre-test = 12.45; post-test = 16.25) [7] and in Indonesia (pre-test = 52 and 100; post-test = 72 and 100) [8].…”
Section: Introductionmentioning
confidence: 55%
“…Their method of teaching grammar is known as the deductive approach. The term "deductive approach" refers to a teachercentered approach in which the teacher explains grammar points by explicitly explaining the details of grammatical pattern to students [18]. Some scholars [19], [20] view deductive approach to be ineffective for improving students' English proficiency because through deductive approach, the learners are typically passive agents with little opportunity to express and practice language.…”
Section: The Knowledge Of Subject Mattermentioning
confidence: 99%